Systematic Literature Review (SLR): Democaracy of Education in the Perspective of Islamic Philosophy of Education - Irwan S; Salminawati Salminawati; Usiono Usiono (Universitas Muhammadiyah Enrekang, 2024)
This research examines the concept of educational democracy from the perspective of Islamic educational philosophy to see how Islamic values ​​and democracy are correlated in education. The aim of this research is to increase our understanding of how democracy can be implemented in an education system that follows Islamic principles. This research is a literature study with the method used, namely Systematic Review (SR) or generally called Systematic Literature Review (SLR). Research shows that combining democracy and Islam in education creates a balanced foundation of freedom, justice and moral obligation. It is hoped that this research can help develop educational policies that are more contextual, relevant and in accordance with Islamic values ​​in the process of building a democratic education system rooted in Islamic values. The results of this research can help practitioners